Targeting nutrient sources and forms to identify yield-limiting nutrients for wheat under contrasting rainfall regimes and landscape positions in mixed-farming systems - Agegnehu, Getachew; Desta, Gizaw; Amare, Tadele; Agumas, Birhanu; Legesse, Gizachew; Amede, Tilahun; Alemu, Erkihun; Bazie, Zerfu; Abera, Abate; Bulo, Fayisa; Demiss, Mulugeta; Degefu, Tulu; et al. (Taylor & Francis, 2025)
Wheat yield gap in Ethiopia is high due to low nutrient availability, soil heterogeneity, undulating landscape, and climate. A study was conducted to identify yield-limiting nutrients for wheat yield under varying landscape positions and rainfall regimes. The treatments included all nutrients in blended (All-Blend), compound (All-Comp), and individual (All-Ind) forms containing N, P, K, S, Zn, and B, while K, S, Zn, and B omitted treatments were (All-Blend)-K, (All-Blend)-S, (All-Blend)-Zn, and (All-Blend)-B. Besides, NP only, 50 and 150% of the rate of all nutrients in the blended form (All-Blend), and a control without any nutrients were included. Results showed that the highest yield was obtained from the application of 150% of All-Blend across landscape positions and rainfall regimes, with grain yield improvement of 109.5% (2.54 t ha−1) by applying 150% of All-Blend under the foot slope position and high rainfall regime compared to the control and yield improvement of 72.5% under the low rainfall regime. With the control treatment grain yield was lower by 27–70% across landscape positions and rainfall regimes. The grain yield penalties due to K, S, Zn, and B omission were 0.54–9% over landscape positions and rainfall regimes compared to applying All-Blend, implying that the omission of K, S, Zn, and B were not yield-limiting nutrients for wheat production in the study areas. Thus, it will be crucial to consider landscape strata and rainfall regimes to optimize NP rates. Further study is also suggested as nutrient applications in blended, compound, or individual forms are inadequate to conclude.